Intraday Trade in Dealership Markets - Dan Bernhardt; Eric Hughson (Queen's University, Department of Economics, 1991)
We develop and test a structural asymmetric information transaction model to characterize the price impact of information on the NYSE. Unlike previous literature, we allow for mixed entry strategies on the part of informed traders and obtain an equilibrium where trades are temporally separated. in addition, when it is costly to transact, informed agents will not trade small quantities. Estimation of the structural parameters is performed using a maximum likelihood procedure. The price impact of information and the average informational innovation are found to be positive and significant. However, when the overidentifying restrictions are tested, the model is rejected with probability one.
Keywords: 330